Exploring public-private partnership (PPP) options for the provision of socialized housing in the Philippines the case of Valenzuela City - Sanchez, Daniela Victoria Sanchez (School of Urban and Regional Planning, University of the Philippines Diliman, 2019)
The Philippines is one of the fastest urbanizing countries in the Southeast Asian Region. Since the 1950s, millions have migrated from rural areas to the cities in search of better job opportunities (World Bank 2016). According to the World Urbanization Prospects 2011 (United Nations 2012), the country is now 50% urban, and by 2025 his proportion is expected to be 805. Metro Manila shows continuing primary when comparing its level of urbanization levels to others regions of the country. Urbanization is one of the most significant drivers of development as it can provide a pathway out of poverty and act as an engine of growth (World Bank 2016). However, accelerated urbanization increases also the demand for housing, basic services and functional transport systems. In the absence of government's intervention, rapid urbanization leads to high levels of urban poverty and rapid expansion of unplanned urban settlements and slums. Though a number of programs have been developed in the Philippines to solve the housing crisis, they have had little impact in resolving the housing needs (World Bank 2016). Due to the magnitude of the problem, the housing program remains inadequate and unable to provide a solution at the scale and quality needed. In terms of scale, there is severe shortage in government funding to adequately address the housing requirements. If any advance is to be made to reduce the country's housing backlog, private sector participation should be encouraged (Corpuz and Cariño 2009). Through Public-Private Partnerships (PPPs), government can supplement the funding available for the housing sector, as well as benefit by engaging the private sector in design, financing, construction, operation and maintenance of the housing assets. Since PPPs have been extensively applied in the Philippines for the development of productive infrastructure but more limited in the social sectors,the aim of this research is to explore how can PPPs be implemented at national and local levels for the provision of affordable, quality and sustainable socialized housing. A review of the socialized housing market and an examination of the challenges faced by the private sector to participate in this sector are presented. Based on international experiences and the review of national framework on PPP, schemes and key attributes that make the provision of socialized housing viable through PPP in the Philippine context are defined. Finally, the viability of implementing PPP at the local level is assessed, according to strategic, economic, commercial, financial and managerial dimensions.Based on the results of the research, it is found that despite private sector's interest to participate in socialized housing, it is constrained to do so due to the low profit margins that characterize this sector. Nevertheless, it is suggested that if the appropriate incentives are in place, private sector may be willing to participate more intensively in several stages in housing production. Two suitable models are proposed for the provision of socialized housing in the Philippine context. However, the selection of each model, shall be determined on a case to case basis, considering the aims and goals of the government agency. At the local level, budget limitations are the greatest challenge for the provision of socialized housing. Since current initiatives on PPPs for socialized housing are being managed at the national level, its support is necessary for the replication of successful partnerships at the local level.